Relationship between the adenosine A1 receptor and cGMP levels in the hippocampus: implications on neurotransmission and synaptic plasticity - Serpa, André Santos Romão Piques (2016)
Submitted by Paulo Pessoa (pfep@ubi.pt) on 2016-02-16T10:00:00Z No. of bitstreams: 1 Tese Completa Junho 2015.pdf: 3070357 bytes, checksum: fe91985a9e3e551bfa5ec985c6cf123c (MD5)